2020
DOI: 10.1021/acsomega.0c05546
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Evaluation of Sanjoseolide and Representative Analogues

Abstract: The first total synthesis of sanjoseolide (1), which was originally obtained from Dalea frutescens A, was achieved via an efficient route with a longest linear sequence of six steps from the commercially available 2,4-dihydroxyacetophenone in 8.6% overall yield. Meanwhile, a series of sanjoseolide representative analogues were synthesized and assessed for their antiproliferative potency against cancer cells of different origins. Compound 8e inhibited the survival of all tested cancer cell lines in a dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Sanjoseolide, a natural product containing an isoprenylated chalcone skeleton, obtained from Dalea frustecens , has wide pharmacological significance, as it has been found to be effective against inflammation, cancer and diabetes [ 100 ]. Owing to its huge medicinal importance, Tian et al [ 101 ] in 2020 reported an efficient method for the synthesis of sanjoseolide by carrying out Sharpless asymmetric dihydroxylation, Stille coupling and Claisen–Schmidt condensation. In the first step, 2,4-dihydroxyacetophenone 208 was treated with I 2 and KIO 3 followed by protection with a methoxymethyl group, leading to the synthesis of compound 209 in 90% yield.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Sanjoseolide, a natural product containing an isoprenylated chalcone skeleton, obtained from Dalea frustecens , has wide pharmacological significance, as it has been found to be effective against inflammation, cancer and diabetes [ 100 ]. Owing to its huge medicinal importance, Tian et al [ 101 ] in 2020 reported an efficient method for the synthesis of sanjoseolide by carrying out Sharpless asymmetric dihydroxylation, Stille coupling and Claisen–Schmidt condensation. In the first step, 2,4-dihydroxyacetophenone 208 was treated with I 2 and KIO 3 followed by protection with a methoxymethyl group, leading to the synthesis of compound 209 in 90% yield.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…10 Another fragment focused on the formation of aryl iodine. 11 Compound 9 was used as a raw material to generate compound 12. It is worth noting that introducing aryl iodide was innovative in the designed synthetic route, because it provides the possibility of adding side chains in the total synthesis of natural products.…”
Section: Synthesis Of Key Intermediate and Core Structurementioning
confidence: 99%
“…(2) Six thermodynamic equations were applied to regress the solid−liquid equilibrium data to obtain model parameters, and the regression effects were evaluated. (3) The KAT-LSER model was employed to study the dissolution rule of 2′,4′-DHAP in monosolvents at room temperature and analyze the relative contribution of various forces to the dissolution process.…”
Section: Introductionmentioning
confidence: 99%
“…In the pharmaceuticals industry, 2′,4′-DHAP can be used as a material to synthesize Schiff bases, paeonol, and efloxate, which have the function of treatment of antiangina pectoris. In the organic synthesis field, 2′,4′-DHAP is applied to synthesize chalcone as an indicator of the organic synthesis process. In addition, 2′,4′-DHAP can be used as an iron ion detection reagent to give ferric chloride solutions a red color …”
Section: Introductionmentioning
confidence: 99%